2021
DOI: 10.1021/acsmeasuresciau.1c00020
|View full text |Cite
|
Sign up to set email alerts
|

Laser Ablation Synthesis in Solution and Nebulization of Silver-109 Nanoparticles for Mass Spectrometry and Mass Spectrometry Imaging

Abstract: Preparation of monoisotopic silver-109 nanoparticles ( 109 AgNPs) by pulsed fiber laser (PFL) ablation synthesis in solution (LASiS) with the use of a 2D galvoscanner (2D GS) is described. The procedure of covering of custom-made stainless-steel MALDI targets containing studied objects via nebulization is also presented. Examples of application of the new method (PFL-2D GS LASiS and nebulization) in mass spectrometry (MS) analyses and MS imaging (MSI) are shown. These include tests with a nonionic nucleoside a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 50 publications
0
20
0
Order By: Relevance
“…Surface roughness [30] and topography have all been effective in microbial biofilm research [31]. A few studies have shown that Bi 2 O 3 NPs have strong antibiofilm actions against various pathogens in vitro and have indicated various antibacterial mechanisms for Bi 2 O 3 NPs, including impairing cell division, disturbing the cell wall cytoplasmic membrane, and decomposing DNA [32][33][34]. By employing AFM image analysis [29], the biofilm formation and surface roughness of P. aeruginosa were investigated by AFM.…”
Section: Viability Assay For Bacterialmentioning
confidence: 99%
“…Surface roughness [30] and topography have all been effective in microbial biofilm research [31]. A few studies have shown that Bi 2 O 3 NPs have strong antibiofilm actions against various pathogens in vitro and have indicated various antibacterial mechanisms for Bi 2 O 3 NPs, including impairing cell division, disturbing the cell wall cytoplasmic membrane, and decomposing DNA [32][33][34]. By employing AFM image analysis [29], the biofilm formation and surface roughness of P. aeruginosa were investigated by AFM.…”
Section: Viability Assay For Bacterialmentioning
confidence: 99%
“…It is also cost-effective, as no other chemicals are required and the silver-109 metal foil can be reused. 15…”
Section: Resultsmentioning
confidence: 99%
“…6 Laser ablation methods have an advantage over chemical synthesis because they allow for very quick synthesis of NPs (several seconds vs. hours in chemical synthesis), and the synthesized NPs are stabilizer-and reducingagent-free. 7 The literature provides many examples of the use of NPs in LMW analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, monoisotopic silver NPs have some additional properties like the simplest possible peak pattern, a much higher intensity of analyte peaks, and simplified calculations of isotopic distribution 6 . Laser ablation methods have an advantage over chemical synthesis because they allow for very quick synthesis of NPs (several seconds vs. hours in chemical synthesis), and the synthesized NPs are stabilizer‐ and reducing‐agent‐free 7 . The literature provides many examples of the use of NPs in LMW analysis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation